EVALUASI PRODUKSI PERIKANAN TANGKAP PELAGIS KECIL DI PERAIRAN PANTAI BARAT SULAWESI SELATAN - Nelwan, Alfa F.P; Sondita, M. Fedi A.; Monintja, Daniel R.; Simbolon, Domu (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Fish production is one of indicators to measure performance of a fisheries. Level of fishing effort will determine the amount of fish production. Dynamics of capture fisheries can be described from fluctuations in fish production, fishing effort and fishing productivity. The capture fisheries in the the western coast of Sulawesi can be distinguished into three fisheries, i.e. The marine area adjacent to the studied coast is divided into three zones, zone A (waters around Kepulauan Spermonde), zone B (Bay of Mandar), and zone C (waters of Majene dan Mamuju Districts). The objective of this research is to compare dynamics of fisheries performance among the three zones. To calculate total fishing effort performed by the entire fishing fleets, standardization of 8 fishing gear was done. This research utilized fisheries data sets covering a period of 30 years (1977-2006). Fishing fleets in each zone showed a negative relationship between fishing effort and the CPUE, i.e higher fishing effort lower CPUE, over the time period. Fisheries performance in each zone was affected by development policy, the fisheries in zones A and B have reached their optimum level earlier than the fisheries in zone C. Fisheries management for each zone should consider local characteristics of fishing fleets and fish resources.